Successful treatment of gonococcal osteomyelitis with one week of intravenous antibiotic therapy. (May 2019) - Gharamti, Amal A; Pinto, Natalia C; Henao-SanMartin, Valentina; Franco-Paredes, Carlos; Henao-Martínez, Andrés F
Gonorrhea is one of the most common sexually transmitted infections (STIs). In a minority of cases, a disseminated infection can occur including gonococcal osteoarticular disease. With the steep and sustained increase in STIs in the US, we could see invasive gonococcal disease more often. Most cases of gonococcal osteomyelitis receive prolonged courses of antibiotic therapy. We report here the successful treatment of gonococcal osteomyelitis with one week of antibiotic therapy. Given the emergence of bacterial resistance worldwide and associated side effects, it is crucial to limit antibiotic exposures to the smallest effective dose possible.